HUBUNGAN TINGKAT PENGETAHUAN RESPONDEN DENGAN PEMILIHAN OPERATOR SELAIN DOKTER GIGI DITINJAU DARI BAHAYA PEMASANGAN ALAT ORTODONTIK - Khairusy, Cecep Hadyan; Adhani, Rosihan; Wibowo, Diana (Dentino, 2017)
Background: Orthodontic treatment is increasingly in demand by the public. Orthodontic treatmentperformed by an operator other than dentists who are competent if itâs not appropriate with properlymaintenance procedures will cause adverse impacts. Purpose: The objectives of this study are knowing therespondentâs level of knowledge about bad impacts of orthodontic mounting and knowing the correlationbetween respondentâs level of knowledge with operator choice beside dentist. Method: This study was anobservational analytical with cross sectional approach. This study was done to 30 students of SMAN 2Banjarmasin. Result: When the study and analyze data were done, the result was most of respondent have levelof knowledge in good category, they were 24 students (80%), Conclusion : There is correlation betweenrespondentâs level of knowledge with operator choice based on bad impacts of orthodontic mounting.Keywords : Level of Knowledge, Operator Choice, Bad Impacts of Orthodontic Mounting